Urinary Citrate Is Associated with Kidney Outcomes in Early Polycystic Kidney Disease. Issue 12 (29th December 2022) - Rocha, Daniel Ribeiro; Xue, Laixi; Gomes Sousa, Hiago Murilo; Carvalho Matos, Ana Christina; Hoorn, Ewout J.; Salih, Mahdi; Heilberg, Ita Pfeferman
Key Points: Low urinary citrate and crystal deposition accelerated cystogenesis in an experimental model of polycystic kidney disease (PKD). Hypocitraturia, frequently observed in patients with autosomal dominant PKD (ADPKD) could contribute to disease progression. Present findings suggest lower urinary citrate in early PKD was associated with faster eGFR decline and worse kidney survival.